A trial comparing nicardipine and cyclopenthiazide K in a group of general practice patients with mild to moderate hypertension - Murray, T. S. (1986)
1 The study was a single-blind, parallel comparison of the effects of nicardipine and cyclopenthiazide-K given to patients with mild to moderate hypertension. Eight principal general practitioners admitted 91 patients. Forty-four were randomised to cyclopenthiazide-K and 47 to nicardipine. Blood pressure was measured using a random zero sphygmomanometer. 2 There were statistically significant decreases in systolic and diastolic blood pressures supine, standing and after hand grip isometric exercise in both groups of patients, relative to baseline. 3 Median blood pressure reduction over the 6 weeks of the study for sitting, standing and post-submaximal exercise in the nicardipine group of patients was 171/105 to 149/88, 167/105 to 144/90 and 175/107 to 152/92 mm Hg respectively. In the cyclopenthiazide-K group patients the changes were 172/105 to 151/94, 168/106 to 149/96 and 178/107 to 159/98 mm Hg respectively. The greater blood pressure reduction on nicardipine relative to cyclopenthiazide-K was statistically significant at week 3 and 6 for supine, standing and post-submaximal exercise diastolic blood pressure and at week 3 for post-submaximal exercise systolic blood pressure. 4 Therapy was assessed by the investigating doctors as excellent, very good or good in 71% of nicardipine patients and in 55% of cyclopenthiazide-K patients. 5 More patients reported side-effects in the nicardipine group (25) than in the cyclopenthiazide-K (16). This may have been related partly to their pre-study therapy. There was some evidence for the acquisition of side-effect tolerance in the nicardipine group. 6 In the nicardipine group there were no changes noted which could be suggested as long-term cardiovascular risk factors, though some (reduced blood potassium, increased uric acid) were seen in the parallel cyclopenthiazide-K group.